Christian Final Year College Student: Preparedness and Consciousness in Adopting Biblical Principles to Survive and Thrive in Exile During the One-Year NYSC Program - Gilbert N, Alaribe; Okwuosa, Lawrence; Uroko, Favour (Jurnal Didaskalia, 2024)
This research aims to investigate the level of awareness and readiness of final year Christian students in adopting a biblical-based exile lifestyle model. Two research questions and two hypotheses were proposed to guide this study. A descriptive survey research design was employed. The sampling technique used proportional multistage stratified random sampling method to obtain a sample size of 340 final year Christian students in State-owned colleges in Imo Province. The researcher-developed assessment scale titled "Christian Students' Awareness and Readiness Scale for Facing Life Challenges in Exile (CAPLCERS)" was utilized for data collection. This assessment scale comprises two clusters, A and B, with internal consistency reliabilities measured using Cronbach's Alpha of 0.78 and 0.82 respectively. Mean and standard deviation were used to answer research questions, while z-test was employed to test hypotheses at a significance level of 0.05. The research findings indicate that the level of awareness among final year Christian students regarding life challenges in exile during the one-year mandatory National Youth Service Corps (NYSC) program is significantly below the expected average. Meanwhile, their readiness level to adopt biblical models for survival and growth in exile is significantly above the expected average. Based on these findings, the research recommends several actions: college authorities need to equip final year students with awareness of potential life challenges they may face during the one-year NYSC program; campus Christian fellowships also need to help prepare their members with biblical models and principles that can assist Christians in surviving and thriving in exile situations; and Christian fellowships or organizations in NYSC training camps need to assist Christian Corps members in integrating and striving for welfare in their placement areas while learning to love and contribute to the growth of communities that may differ in beliefs and cultures.